The effects of a hypertension diagnosis on health behaviors: A two‐dimensional regression discontinuity analysis - Dai, Tiantian; Jiang, Shenyi; Liu, Xiangbo; Sun, Ang (Health economics, 2022)
This paper explores how a diagnosis of hypertension might affect a person's health‐related behaviors. The analysis uses a two‐dimensional regression discontinuity design because hypertension is diagnosed when a person's systolic or diastolic blood pressure (SBP or DBP) surpasses a pre‐established threshold. We find that those closely above the SBP threshold significantly adjusted their lifestyle, such as reducing daily fat intake and quitting smoking, while those just surpassing the DBP cutoff did not. Further mechanism analysis suggests that the possibility of constraints, rather than education and income gradients, does more to explain the disparate behaviors of subjects near the SBP and DBP thresholds. Those around the DBP threshold generally have tighter work schedules and undertake more competitive jobs, which hinder them from improving their lifestyle. Overall, our findings complement the existing literature by posing a new perspective for understanding people's potential reluctance to adjust their behavior.